Outstanding Referee of the American Physical Society - Kelires, Pantelis C. (My University, 2026)
American Physical Society announces "Outstanding Referees" for 2016 Contact: Eunice Toro, American Physical Society, eunice@aps.org, 631-591-4047 Ridge, NY, 19 February 2016 — The American Physical Society (APS) has selected 146 Outstanding Referees for 2016 that have been exceptionally helpful in assessing manuscripts for publication in the Physical Review journals. The decisions were difficult and there are many excellent referees who remain to be recognized. A full list of the Outstanding Referees for 2016 is available online at http://journals.aps.org/OutstandingReferees. The selection this year was made from 30 years of records on over 69,000 referees who have been called upon to review manuscripts, including more then 37,200 that were submitted in 2015. The basis for selection includes the quality, number and timeliness of their reports, without regard for membership in the APS, country of origin, or field of research. Individuals with current or very recent direct connections to the journals, such as editors and editorial board members, were excluded. The 2016 honorees come from 27 different countries, with large contingents from the U.S., Germany, U.K., Canada, and France. All have been notified, and have been sent a lapel pin and a certificate. The Outstanding Referees are to be congratulated and thanked for their outstanding service to the physics community. The Outstanding Referee program annually recognizes approximately 150 of the currently active referees, although larger groups were recognized in the first two years of the program. Like Fellowship in the APS and other organizations, this is a lifetime award. In initiating the program, APS expresses appreciation to all referees, whose efforts in peer review not only keep the standards of the journals at a high level, but in many cases also help authors to improve the quality and readability of their articles—even those that are not published by APS. About APS: The American Physical Society (www.aps.org) is a non-profit membership organization working to advance and diffuse the knowledge of physics through its outstanding research journals, scientific meetings, and education, outreach, advocacy and international activities. APS represents 53,000 members, including physicists in academia, national laboratories and industry in the United States and throughout the world. Society offices are located in College Park, MD (Headquarters), Ridge, NY, and Washington, DC.
Keywords: Sciences